[PP.12.20] ANTIANGIOGENIC CYSTEINE-KNOT MINIPROTEINS PRESENT IN TOMATO FRUITS AND INDUSTRIAL DERIVATIVES CAN BE ABSORBED THROUGH THE GASTROINTESTINAL MUCOSA. (September 2017) - Minuz, P.; Treggiari, D.; Dalbeni, A.; Molesini, B.; Chignola, R.; Zoccatelli, G.; Pandolfini, T.
Abstract : Objective: Tomato fruit is rich in compounds with potential biological activities. We previously identified in tomato fruit two cystine-knot miniproteins (TCMP-1 and -2) endowed with antiangiogenic activities (Cavallini Br J Pharmacol 2011). We tested purified TCMPs (200 nmol/L) on human umbilical vein endothelial cells (HUVEC) migration, a critical step in the angiogenesis. The scratch assay showed that TCMP-2 inhibits by 50% the increase in cell migration induced by VEGF-A. TCMP-2 inhibited VEGFR2 phosphorylation and reduced NO release in HUVEC by 34%. TCMPs inhibited the formation of subintestinal vessels in zebrafish embryos that is controlled by VEGF (Treggiari Mol Nutr Food Res 2015). The present study aimed at defining the pharmacological potential of TCMPs by assessing their oral bioavailability, and estimating the potential dietary intake determining TCMPs concentration in tomato fruits and derivatives. Design and method: We investigated whether TCMPs are absorbed by gastrointestinal apparatus and endure industrial processing without losing their biological activity. The resistance of TCMPs extracted from mature fruits to proteolytic attack was studied in vitro testing simulated gastrointestinal fluids. To explore the intestinal transport of TCMPs we used the differentiated Caco-2 cells model. Finally, we developed a method for purifying TCMPs from tomato paste to assess the effects of the industrial processing on TCMPs biochemistry and bioactivity. Results: The gastric proteases did not produce TCMP fragmentation, indicating that the purified TCMP is resistant to gastro-intestinal proteases. After 24 h incubation, 37.73 ± 9.34% of TCMPs crossed the epithelium, without altering the integrity of the Caco-2 cell layer. We found appreciable amounts of TMCs in different tomato varieties (48.89 ± 0.07 to 61.68 ± 0.07 mg/g FW) and tomato paste. Conclusions: In conclusion, besides the effects of lycopene and other tomato antioxidants, TCMPs may exert beneficial effects for disease prevention and treatment such as diabetic retinopathy, which is characterized by aberrant formation of vessels, caused by enhanced migration of endothelial cells. The strong resistance to gastric and intestinal proteolysis and the high rate of intestinal absorption of TCMPs offer opportunities for oral administration.